2014
DOI: 10.1007/s13524-013-0271-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors Shaping Workplace Segregation Between Natives and Immigrants

Abstract: This is the published version of a paper published in Demography. Citation for the original published paper (version of record):Strömgren, M., Tammaru, T., Danzer, A., van Ham, M., Marcińczak, S. et al. (2014) Factors shaping workplace segregation between natives and immigrants. Abstract Research on segregation of immigrant groups is increasingly turning its attention from residential areas toward other important places, such as the workplace, where immigrants can meet and interact with members of the nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
1
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 69 publications
8
60
1
5
Order By: Relevance
“…Our work also complements very recent contributions to the population studies literature on occupational segregation and workplace concentration (Andersson et al 2014;del Rio and Alonso-Villar 2015;Stromgren et al 2014). We believe that our genuine contribution is the multidimensional characterization of workplace skills of jobs that immigrants sort into, rather than occupation labels per se.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Our work also complements very recent contributions to the population studies literature on occupational segregation and workplace concentration (Andersson et al 2014;del Rio and Alonso-Villar 2015;Stromgren et al 2014). We believe that our genuine contribution is the multidimensional characterization of workplace skills of jobs that immigrants sort into, rather than occupation labels per se.…”
supporting
confidence: 54%
“…Our work contributes to the recent population studies' literature on occupational segregation and workplace concentration among immigrants (Andersson et al 2014;del Rio and Alonso-Villar 2015;Stromgren et al 2014). The empirical evidence presented here helps characterize the skill dimensions of jobs into which immigrants sort, going much deeper than occupation labels.…”
Section: Discussionmentioning
confidence: 68%
“…Numerous studies in sociology and geography have highlighted the critical role that formal work organizations play in bringing individuals of different national cultures into contact with each other (e.g., Ellis, Wright, & Parks, ; Rogers, ). While residential spaces tend to be segregated across minority groups, workplaces bring together employees from a broader section of society (Strömgren et al, ). For example, empirical accounts have shown that racial diversity in Chicago steel mills provided avenues for meaningful intergroup contact across otherwise impermeable social boundaries along the city's neighborhoods (Kornblum & Janowitz, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Both labour market and residential segregation between ethnic groups tends to be persistently high in European cities (Strömgren et al . ; Tammaru et al . ).…”
Section: Ethnic Segmentation Segregation and Interaction During Leismentioning
confidence: 99%